Transnational migration, gender and rights - Leonard, Liam.; Sollund, Ragnhild Aslaug, 1959-; Emerald eBooks (Bingley, U.K. : Emerald, 2012)
The last decades have shown an increase in the migration from poor and conflict ridden states to the affluent peaceful north. Part of this migration is constituted by refugees and asylum seekers, while the other part, grossly put, is constituted by labour migrants who seek to improve their lives and future prospects through their work power. There are of course not only push factors causing migrants to leave, but also pull factors as when the middle classes enjoy an increase in their living standards which cause them to employ domestic help in their homes. Different regulations apply for migrants within different national contexts and also within the same nation and have different impact on the migrants manoeuvring possibilities and rights, and may leave them vulnerable to exploitation. As migration is gendered in that different motivations often exist for men and women, so are the possibilities that are offered, exemplified by the fact that very many women migrate as domestic workers, as nannies, or as au pairs, yet basically perform the same duties but are defined differently according to the rules that apply. As the work the female migrants perform is very often and traditionally regarded as womens work it does not qualify as real work and, consequently, it is not necessary to pay them a proper salary. This book examines the vulnerability caused by migration or rather the fact that the vulnerability of women may cause a forced migration and the ways in which this is dealt with by national authorities in affluent European states.
ch. 1. Introduction : manoeuvring rights : immigrants' experiences of inclusion and exclusion / Ragnhild Aslaug Sollund -- ch. 2. EU mobility partnerships and gender : origin and implications / Meng-Hsuan Chou -- ch. 3. Gendered work and migration regimes / Rosie Cox -- ch. 4. Deprofessionalisation and informality in the market for commoditised care / Nicky Busch -- ch. 5. The essence of food and gender and the embodiment of migration / Ragnhild Sollund -- ch. 6. 'A slow assassination of your soul' : race, citizenship and gender identities in the borderlands of new economic places / Elizabeth L. Sweet, Sang S. Lee, Sara Ortiz Escalante -- ch. 7. Exploring intersectionality, systems and capitals : the case of a Filipino nurse in Norway / Marie Louise Seeberg -- ch. 8. at a crossroads : youth at the intersection of the family and the state / Lauren Heidbrink -- ch. 9. From liberalism & democratization to trafficking : America's spiralling problems and still-aspiring controls / Imtiaz Hussain -- ch. 10. Moving beyond assumptions? : the framing of anti-trafficking efforts in Norway / May-Len Skilbrei -- ch. 11. Difficult victims : perceptions of Nigerian victims of trafficking in Norway / Julie Estdahl Stuestl.
Keywords: Nature -- General; Nature -- Environmental Conservation & Protection; Business & Economics -- Environmental Economics; Environmentalist thought & ideology; Migration, immigration & emigration; Transnationalism; Women immigrants; Electronic books